Pelaksanaan Restrukturisasi Kredit Dampak Pandemi Covid-19 (Studi BPR Kanti Batubulan) - I Made Krisnan Wijaya Putra; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2022)
The provision of credit provides many opportunities for job creation, because credit has provided an opportunity for the community to develop a business that is offered. In the current state of the covid-19 pandemic, in banking, many loans are categorized as credit due to the impact of the covid-19 pandemic. This is due to the widespread decline in the ability to pay debtors to banks, from the decline or inability of debtors to pay. The purposes of this study are to reveal the application of credit restructuring due to the COVID-19 pandemic at BPR Kanti Batubulan and the legal consequences of implementing credit restructuring due to the COVID-19 pandemic at BPR Kanti Batubulan. The method used in this research is empirical legal research with a conceptual and sociological case approach. Data collection techniques were carried out by observation and interviews. The sources of legal materials used are secondary and primary legal sources which are presented qualitatively. The results of this study show that the level of effectiveness of Credit Restructuring due to the COVID-19 pandemic at BPR Kanti Batubulan is quite effective, this is evidenced by a decrease in the number of credit restructurings impacted by the COVID-19 pandemic from 2020 to 2021.